Assessment of Multi-Nutrients and Heavy Metals in Inorganic Fertilizers Widely Used by Indonesian Farmers Using NAA - Sri Juari Santosa; Roto Roto; Sri Murniasih (Indonesian Journal of Chemistry, 2022)
This research aims to determine the concentration of multi-nutrients and heavy metals and investigate the correlation among them in the seven inorganic fertilizers in Indonesia. Sample analysis was carried out using the NAA method. The highest concentrations of macro-nutrients were K (36.54 %) and Cl (18.09%) found in the KCl sample, while Ca (23.01%) was observed in the TSP sample. In the case of micro-nutrients, the highest concentrations of Se (0.36 mg/kg), Ti (597 mg/kg), Br (1.84%), and Ni (2.46 mg/kg) detected in the NPK sample. Meanwhile, the highest concentrations of Co (19.57 mg/kg) and Na (1.40%) were measured in the ZA sample, while Mg, with the highest concentration of 1.78%, was found in the KMgS sample. The micro-nutrients with the highest concentration detected in the TSP sample were Cr (45.96 mg/kg), Zn (342.6 mg/kg), and Mn (1331 mg/kg). Non-essential elements such as U, V, La, Sb, Sm, Th, Hf, Sr, Cs, Tb, Sc, Rb, Ta, and Eu were also detected in the fertilizer samples with the highest concentrations in the TSP sample. Statistical tests of multi-nutrient and heavy metals concentrations indicated that multi-nutrient and heavy metals in fertilizers are complex.